Challenging Epistemic Hegemony: Islam, Memory, and the Struggle over Southeast Asian History - Hana Lestari; Raden Yusuf Firmansyah; Syed Imran Syed Hassan (Tunas Harapan Ummat Foundation, 2025)
The historical discourse on Southeast Asia often centers on the introduction, dissemination, and impact of Islam within the Malay-Indonesian Archipelago. Scholars continue to debate whether Islam first entered the region in the 13th century or at an earlier time; whether its origins were rooted in India or came directly from Arabia; and whether its spread was primarily driven by merchants, wandering Sufi mystics, or organized missionaries. Another key question is whether conversion to Islam merely overlaid the existing cultural fabric while leaving traditional practices largely intact, or whether it fundamentally reshaped society’s structures and worldview. This article aims to “decolonize” the historiography of Islam’s arrival and influence in the Malay world by re-examining the claims of European Orientalists alongside those of so-called “Revisionist” historians. The latter have introduced new evidence and reinterpretations that seek to challenge established narratives, distinguish historical fact from constructed myth, and reframe the debate on Islam’s role in shaping the region.